Flow Velocity Effect on Clear Water Bridge Pier Scour - Yeleğen, Mehmet Öner; Uyumaz, Ali (Avestia Publishing, 2016)
For a long while, scour mechanism has been a major problem to be solved by many researchers. Local scour phenomenon at bridge piers has many parameters such as flow characteristics, sediment type, bridge pier shape and alignment. To find a general scour equation under the same conditions, the effect rate of any parameter has to be determined. After the determination phase, the rectifier coefficients for a valid equation can be easily calculated for scour estimation. In order to specify whether the scour condition is clear-water or live-bed, the velocity parameter has to be substituted into scour equations because the determinative factor between these two conditions is the flow velocity. Accordingly in this study, the effect of the ratio of mean approach flow velocity to the critical mean approach flow velocity for entrainment of bed sediment (V/Vc) has been investigated. Three of the mostly used empirical scour formulations, did not take into account the flow velocity, but they are rectified to verify this effect. The data set belongs to four previous studies. Since the parameter, V/Vc, is a dimensionless factor the physical characters of these equations are not altered significantly. However, importation of this parameter into the currently available formulations improves the calculation results in significant manner.
Keywords: Scour; Clear Water; Velocity Effect; Bridge Pier; Zero-Dimensional